Macrozoobentos Diversity as A Bioindicator of Water Quality in Poso Lake, South Pamona District, Poso Regency and Its Utilization as A Learning Media - Selvianita Selvianita; Syech Zainal; Bustamim Bustamim (Equator Science Journal, 2024)
Macrobenthos are animals that live at the bottom of waters, both freshwater and seawater. This study aims to describe the diversity of macrobenthos as a bioindicator of water quality in Lake Poso and its use as a learning medium. This study uses a purposive random sampling method with a sampling technique using free collection with a roaming path method of ± 100 m per station. While the data analysis technique uses quantitative descriptive. The results of the study showed that the macrobenthos diversity index was obtained at station I (2.51) and then followed by station II (2.44) and station III (2.19). While the macrobenthos diversity index in Lake Poso is 2.26 and is categorized as a moderate level of diversity. The high macrobenthos diversity index at station I is because the macrobenthos habitat is still maintained and surrounded by forest vegetation so that the macrobenthos found are quite diverse. The development of research results as a learning media in the form of a pocket book, from the validation results including media validation, content validation, and design validation conducted by 3 expert lecturers and the feasibility test tested on 20 students obtained a percentage of 79.6% and is worthy of being used as a learning media.